Information Remedies for Consumer Protection - Beales, Howard; Craswell, Richard; Salop, Steven C. (American Economic Review, 1981)
Consumer protection regulation has come under increasing fire from the Congress, courts, and the business community. In response, regulators have begun to innovate with market interventions that are more compatible with economic incentives. These incentive-compatible techniques include establishing property rights, mandating performance standards (instead of design standards), increasing competition, and encouraging and mandating information disclosure. Information disclosure allows consumer self-protection, compatible with individual preferences. Information is also compatible with sellers' incentives, inducing them to compete on the basis of information disclosed. In addition, this competition increases the incentive to generate and disseminate additional product information, thereby repeating the cycle. In this way, information remedies rely on private economic incentives to achieve regulatory goals, rather than on expensive direct enforcement by the regulator. Diagnosis of an information problem and evaluation of alternative remedies requires a number of steps: analysis of information production and distribution, identification of market failures and their implications for resource allocation in the information and product markets, and analysis of alternative remedies in light of these market failures.